Acute Pain Is Associated With Chronic Opioid Use After Total Knee Arthroplasty. Issue 7 (1st October 2018) - Hsia, Hung-Lun; Takemoto, Steven; van de Ven, Thomas; Pyati, Srinivas; Buchheit, Thomas; Ray, Neil; Wellman, Samuel; Kuo, Alfred; Wallace, Arthur; Raghunathan, Karthik
Abstract : Background and Objectives: Pain scores are routinely reported in clinical practice, and we wanted to examine whether this routinely measured, patient-reported variable provides prognostic information, especially with regard to chronic opioid use, after taking preoperative and perioperative variables into account in a preoperative opioid user population. Methods: In 32, 874 preoperative opioid users undergoing primary total knee arthroplasty at Veterans Affairs hospitals between 2010 and 2015, we compared preoperative and perioperative characteristics in patients reporting lower versus higher acute pain (scores ≤4/10 vs >4/10 averaged over days 1–3). We calculated the propensity for lower acute pain based on all available data. After 1:1 propensity score matching, to identify similar patients differing only in acute pain, we contrasted rates of chronic significant opioid use (mean >30 mg/d in morphine equivalents) beyond postoperative month 3, discharge prescriptions, and changes in postoperative versus preoperative dose categories. Sensitivity analysis examined associations with dose escalation. Results: Rates of chronic significant opioid use (21% overall) differed in patients with lower versus higher acute pain (36% vs 64% of the overall cohort). After propensity matching (total n = 20, 926 patients) and adjusting for all significant factors, lower acute pain was associated with less chronic significant opioid use (rates 12% vs 16%), smaller discharge prescriptions (ie, supply <30 days and daily oral morphine equivalent <30 mg/d), and more reduction in dose, all P < 0.001. In sensitivity analysis, dose escalation was 15% less likely with lower acute pain (odds ratio, 0.85; 95% confidence interval, 0.80–0.91). Conclusions: Acute pain predicts chronic opioid use. Prospective studies of efforts to reduce acute pain, in terms of long-term effects, are needed.